Hologram technology as an input to enrich the aesthetic values of design in contemporary plastic art. (Al-Academy, 2024)
The study aimed to identify the concept of hologram technology, clarify the aesthetic values ​​of design in contemporary plastic art, identify the concept of contemporary plastic art, study models of holographic works in contemporary plastic art, and to achieve this, the descriptive analytical approach was used by addressing hologram technology and the aesthetic values ​​of design and contemporary plastic art. The study reached many results, namely that the use of modern technological techniques such as hologram technology contributes to highlighting the aesthetic values ​​of design in contemporary plastic art, and that hologram technology has many aesthetic dimensions that contribute to the development and enrichment of the aesthetic form of contemporary plastic art, and that the diversity of technological methods and techniques used in contemporary artworks contributes to enriching aesthetic values. The study reached several recommendations, represented in paying attention to studying the potential of hologram technology in enriching contemporary plastic art, conducting a study on more hologram works by contemporary artists, developing art students to understand and comprehend modern technological techniques, and the necessity of educating society in the aesthetic values ​​of contemporary plastic art